Knowledge and Skill in Relation to the Speed and Accuracy of the Nurses When Assessing Using an Early Warning System (EWS) - QolbiNur Q.Y; Nursalam Nursalam; Ahsan Ahsan (Jurnal Ners, 2020)
Introduction: Errors when filling in or interpreting the results of the EWS assessment causes delays and inaccuracies for the nurses when providing a clinical response. The aim of this study was to explain the relationship between the nurse’s knowledge and skill with the speed and accuracy of the nurse when assessing via EWS.Methods: This study used a correlation design with a cross-sectional approach. The sample consisted of 104 nurses working in the inpatient ward of internal medicine according to the inclusion criteria. The sample was obtained through purposive sampling. The independent variable was the nurses’ knowledge and skill while the dependent variable was the nurse’s speed and accuracy when assessing using the EWS. The instruments used were questionnaires and observation sheets. The data was analyzed using Spearman Rho.Results: The results of the study showed that there was a very strong correlation between the knowledge-accuracy of the nurses when assessing using the EWS (r = 0.805; p = 0.000) and the nurse's skill-accuracy when assessing using the EWS (r = 0.823; p = 0.000). There was a strong correlation between the knowledge-speed of nurses assessing using the EWS (r = 0.269; p = 0.006) and the nurse's skill and speed when assessing using the EWS (r = 0.262; p = 0.007).Conclusion: The nurse’s knowledge and skill has a stronger relationship with accuracy when assessing using the EWS when compared to the nurses' speed.